Pengembangan Media Pembelajaran Powerpoint Interaktif Pada Materi Sistem Pencernaan Manusia Kelas V SDN 011 Lenggadai Hulu Kabupaten Rokan Hilir - Sundari, Sundari; Fitriyeni, Fitriyeni (Jayapangus Press, 2025)
One of the efforts that can be made to make the learning process more engaging and meaningful is through the use of instructional media such as PowerPoint. This study aims to develop interactive PowerPoint-based learning media for fifth-grade science material with the topic